2016
DOI: 10.1016/j.neuroimage.2016.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin modulates encoding-related brain function without enhancing memory formation in humans

Abstract: Ghrelin regulates energy homeostasis in various species and enhances memory in rodent models. In humans, the role of ghrelin in cognitive processes has yet to be characterized. Here we show in a double-blind randomized crossover design that acute administration of ghrelin alters encoding-related brain activity, however does not enhance memory formation in humans. Twenty-one healthy young male participants had to memorize food- and non-food-related words presented on a background of a virtual navigational route… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…Moreover, in animals, ghrelin regulates hippocampal spine synapse density and long-term potentiation and enhances spatial learning and memory [ 89 ]. However, Kunath et al [ 90 ] did not find any evidence for the potential of ghrelin acting as a short-term cognitive enhancer in humans. It has been found that viewing food pictures does not affect total calorie intake and ghrelin levels, but improves postprandial glucose levels [ 91 ].…”
Section: Ghrelin Influences the Hedonic And Incentive Responses To Comentioning
confidence: 99%
“…Moreover, in animals, ghrelin regulates hippocampal spine synapse density and long-term potentiation and enhances spatial learning and memory [ 89 ]. However, Kunath et al [ 90 ] did not find any evidence for the potential of ghrelin acting as a short-term cognitive enhancer in humans. It has been found that viewing food pictures does not affect total calorie intake and ghrelin levels, but improves postprandial glucose levels [ 91 ].…”
Section: Ghrelin Influences the Hedonic And Incentive Responses To Comentioning
confidence: 99%
“…However, the exact nature of the relationship between ghrelin and cognitive function in healthy subjects is still unclear, since plasma ghrelin levels have been reported to rather be inversely associated with cognitive function in elderly non-demented patients [181]. Additionally, a more recent study in healthy young subjects concluded that, in contrast to the animal data, acute ghrelin administration did not enhance any parameters of cognitive function, including memory, mental speed or attention [182]. …”
Section: Neurodegenerative Disordersmentioning
confidence: 99%
“…Consistent with this proposal, ghrelin administration to humans has been reported to enhance memory for food compared to non-food pictures in a simple recognition paradigm ( Malik et al, 2008 ) and increase hippocampal activation while viewing food pictures ( Goldstone et al, 2014 ). However, a recent study failed to identify an effect of ghrelin on either spatial memory encoding or consolidation ( Kunath et al, 2016 ) and there appears to be no clear relationship between cognitive function and serum ghrelin levels ( Gahete et al, 2011 ; Spitznagel et al, 2010 ; Stoyanova, 2014 ; Theodoropoulou et al, 2012 ). There is much still to learn about the potential cognitive enhancing effects of ghrelin in humans.…”
Section: Ghrelin and Cognitionmentioning
confidence: 99%